2020
DOI: 10.29086/jisfteh.8.e15
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Skills Sets for Telecare Service Staff in the Context of Digital Health

Abstract: Telecare services have an established place within the United Kingdom. Through using online technologies to help mostly older people to remain at home, they are recognised as having a support role for health as well as social care. This positions telecare services within the broader realm of ‘digital health’. As that position becomes more embedded, it poses questions about the nature of tasks that are (or should be) undertaken by telecare staff, and regarding the knowledge and skills that are required. A conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Telecare emergency response services too have been the focus of limited research, even though those working as ‘first responders’ perform ‘embodied care’ and ‘body work’, attending vulnerable people at times of crisis. Over time, the support required of responders has become increasingly medicalised, initially replacing on‐site wardens in sheltered accommodation who provided out‐of‐hours support with job roles that now include the need for first aid training (Fisk et al, 2020 ). Response services are not minor players in telecare systems, with just over half of local authorities surveyed ( n = 79; Steils et al, 2020 ) commissioning their own instead of relying on unpaid carers or the emergency services.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Telecare emergency response services too have been the focus of limited research, even though those working as ‘first responders’ perform ‘embodied care’ and ‘body work’, attending vulnerable people at times of crisis. Over time, the support required of responders has become increasingly medicalised, initially replacing on‐site wardens in sheltered accommodation who provided out‐of‐hours support with job roles that now include the need for first aid training (Fisk et al, 2020 ). Response services are not minor players in telecare systems, with just over half of local authorities surveyed ( n = 79; Steils et al, 2020 ) commissioning their own instead of relying on unpaid carers or the emergency services.…”
Section: Resultsmentioning
confidence: 99%
“…Over time, the support required of responders has become increasingly medicalised, initially replacing on-site wardens in sheltered accommodation who provided out-of-hours support with job roles that now include the need for first aid training (Fisk et al, 2020). Response services are not minor players in telecare systems, with just over half of local authorities surveyed (n = 79; Steils et al, 2020) commissioning their own instead of relying on unpaid carers or the emergency services. Just as recent research found unpaid carers are treated as 'resources' whose involvement is taken for granted when they provide the response for telecare services (ibid.…”
Section: Telecarementioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the pandemic, despite increases over time in the use of virtual client encounters in clinical practice, telepractice education had remained limited across health professions [15,16]. Given the pre-existing rise in telepractice service delivery and the now massive increase in its use due to the pandemic, the necessity for telepractice education within health profession programs has become pertinent for students to meet graduation requirements and market needs as they enter the workforce.…”
Section: The Importance Of Telepractice Education and Outcome Measure...mentioning
confidence: 99%